If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4n-6(n-3)=24
We simplify the equation to the form, which is simple to understand
4n-6(n-3)=24
Reorder the terms in parentheses
4n+(-6n+18)=24
Remove unnecessary parentheses
+4n-6n+18=+24
We move all terms containing n to the left and all other terms to the right.
+4n-6n=+24-18
We simplify left and right side of the equation.
-2n=+6
We divide both sides of the equation by -2 to get n.
n=-3
| x-4=256 | | x-4=1256 | | 3(g-1)+7=3g | | 7x+5-6x=-21 | | x+10=-14+3x | | 2y^2+8y+6=y^2+6y+9 | | 6x+2=7x-7 | | 6(x-2)=76-5x | | x*y=20 | | 3w+6=9w-30 | | 8+5x=2x+38 | | 4x^2=15x+4 | | x^2-7x-28=-5x-4 | | (4v+2)(4-v)=0 | | .125x+1=-5 | | 11x+7y=17 | | 3(2u-5)=2(3u+4)-(u+8) | | -7x-11=2x+25 | | 271-2x=43x+16 | | Solverd=rt | | 5-10x=20x-17x | | u^4w^4-81w^4=0 | | 5x-4-3x=3x-1 | | (.04)x+2=5x | | 10=5x-4 | | 0.6(x-4)=11.4 | | 43-3x=6x+20 | | -2+3j=4 | | 4x+2=2+2x | | x+49+2x=13-4x | | 12x-4=21x+2 | | 5x-43=3x-13 |